Rancang Bangun Purwarupa Pemilah Nanas Berdasarkan Tingkat Kematangan Menggunakan Mikrokontroler Blue Pill STM32F103C8T6 - Friska Tiara Desy; Arif Surtono; Amir Supriyanto; Junaidi Junaidi (Journal of Energy, Material, and Instrumentation Technology, 2020)
The research about a design of prototype automatic pineapple sorting has been done with a belt conveyor system using a Blue Pill STM32F103C8T6 microcontroller. This research was conducted to create a prototype that can sort pineapples based on maturity level by classified unripe, ripe, and fully ripe. Sorting pineapple against the pineapple ripeness classification was carried out by a simulation process using serial data of index maturity sent from the PC monitor serial to microcontroller via serial communication. The serial data sent in character format was an integer 1; 2; 3; 4; 5; 6; and 7. The conveyor using a chain with gear transmission system and a DC motor as a drive. The results showed that the instument is capable of carrying a maximum load of pineapple fruit of 1.0 kg with a transport speed of 27,98 cm/s and can perform pineapple ripeness sorting with an accuracy more than 90%.